PENGARUH RELATIONSHIP MARKETING, SUASANA KAFE, DAN KEPUASAN PENGUNJUNG TERHADAP LOYALITAS PELANGGAN MOKKA COFFEE ENDE - Maria Helena Carolinda Dua Mea; Yulius Laga (Jurnal MEBIS (Manajemen dan Bisnis), 2021)
This study aims to measure the Effect of Relationship Marketing, Café Atmosphere, and Visitor Satisfaction on Customer Loyalty in Mokka Coffee Ende with a total sample of 50 people determined based on the condition of customers who have visited or by the Accidental Sampling method. Data were analyzed using Smart PLS 3.0 to test the validity and reliability, the amount of outer loading and the value of VIF. Also, bootsraping data is performed to see the effect on the path coefficient analysis and the R-square value. The dependent variable in this study is customer loyalty, while the independent variable consists of relationship marketing, cafe atmosphere and visitor satisfaction. The results of data analysis showed that hypothesis testing conducted on customer loyalty did not have too large influence on relationship marketing variables, the atmosphere of the cafe, and visitor satisfaction. Its influence was only 41 percent while 59 percent was influenced by other variables not examined. The effect of each variable, including relationship marketing variables was by 54.3 percent on customer loyalty. The atmosphere of the cafe had an influence of 37.1 percent. While visitor satisfaction had a negative influence of 13.9 percent on customer loyalty at Mokka Coffee.